A practical commentary on the gospel according to St Mark - Morison, James, 1816-1893 (London, UK Hodder and Stoughton, 1900)
Includes index.
First published 1873. Donated by the late Thomas Denton.
Keywords: Bible. N.T. Mark -- commentaries